Orientation of Human Capital through the Work Competency Approach in a Colombian Company - Vega Riaño, Hugo Alexander (2015)
This study develops the concept of human capital taken as a symbol of value, making references to the importance of people in any organization. Here the great price that is in each one of the members of a company, the man at the center, who each of the parties revolve around in systemic pursuit of excellence are highlighted. Moreover, as the human capital increase their knowledge grows its potential. On the basis of all human capital are the attitudes; in these, people’s behaviors can be modified. Therefore, it is a very important commitment in the case of a head as it comes to play a significant role the inner world of human resources and their relationship with others. Therefore, this study develops a process that guides the human capital to Colombian businesses and foundations to propose strategies for skills development for employees and workers (traditional approaches, competency-based approaches); this leads us to analyze and identify the general basis on which rests the management of human capital in the Colombian company. The competency approach was used for the study, coordinating the various sources and forms of inquiry, from the environment to labor daily, starting from the logic of the actors involved, labor practice and management strategies human capital used in the Colombian company to reach a labor competency training strategies. Human capital management taking into account the competencies, conceived as a synthesis of practice and theory, is one of several options the modern world against the huge gap between formal education, schooling. From this perspective, human capital management must be conceived, as a program to ensure that the individual has the skills, abilities, knowledge, skills and experience requires a company to take specific charge process.